Compounds 7-Hydroxy-6-Metoxic Cytotoxic Cytotoxic Stem Leather From Chisochetonmacrophyllus (Meliaceae) Bark - Mellisa Rodrigo (GoAcademica Research & Publishing, 2020)
A phenyl propanoid compound, 7-hydroxy-6-methoxycoumarin has been isolated from the bark of Chisocheton macrophyllus (Meliaceae). The chemical structure of isolated compound was identified on the basis of spectroscopic data including UV, IR, 1D-NMR, 2D-NMR and mass along with comparison with those spectral data previously reported. 7-hydroxy-6-methoxycoumarin compound showed cytotoxic effect against P-388 murine leukemia cell with IC50 value of 16.5 mg/mL. 7-hydroxy-6-methoxycoumarin compound was reported for the first time from genus of Chisocheton.